ANALISIS KEPUASAN KERJA KARYAWAN BERDASARKAN HUMAN RESOURCE INDEX (HRI) - Luhur Prayogo; B. Adi Suryo Pranoto; Humiras Hardi Purba (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2016)
The objective of this research is for describe about employee satisfaction in three of Unit Bisnis at BM*.This topics also for identification many problems of employee satisfaction in BM* and to give suggestfor improvement of performance management in this company. Metodology on this research is using asurvey, because this method very objective and efficient. Questionnaire besed on Human ResourceIndex (HRI) with measure 15 attribut. Based on survey HRI of employee in BM* is 3,44. This show thatemployee satisfaction in BM* is over the standard (> 3) or high. But some of attribute show the HRIwhich under standard (< 3). Some of this is management quality, organisatin structure and path career,and also company objective. The three of these attribute is problem which need concern on thiscompany.